A new surgical technique "cervical internal os plasty" in cesarean delivery for placenta previa accreta: A case–control study. Issue 9 (March 2019) - Huang, Guiqiong; Wang, Xiaodong; Yu, Haiyan; Zhou, Shu
Abstract : Abstract: Placenta previa accreta is an obstetrical complication that severely affects the heath of the fetus and the mother due to massive hemorrhage during pregnancy. This study reported a new suture technique called "cervical internal os plasty" to control obstetrical hemorrhage in cesarean delivery for patients with placenta previa accreta and retrospectively evaluated the safety and effectiveness of the new technique. From January 2012 to May 2018, we collected 56 patients with this new suture technique, which repaired the damaged weak area with bleeding from the placental attachment site in the lower uterine segment, and restored the damaged anatomic internal os of the cervix. Meanwhile, we compared it with 60 cases with other conservative methods described by other obstetricians with the same qualifications. The perioperative outcomes (blood loss, blood transfusion, operative time, other applied medical technology, and so on) between the 2 groups were recorded in this report. There were no significant differences between 2 groups among age, gravidity, parity, gestational age, and previous dilatation and curettage techniques ( P  > .05). Of the patients with placenta previa accrete, 77.6% (90/116) had previous dilatation and curettage. The comparison between study group and control group on the rate of postpartum hemorrhage, blood transfusion, and mean operative time, average hospitalization days after cesarean delivery, expenses was not statistically significant ( P  > .05). Compared with the control group, other applied supplementary techniques (including uterine tamponade, pelvic arterial embolization, or emergency hysterectomy) for the bleeding from the the placental attachment site is fewer significantly in the study group. No operative accident and hemorrhea-related complication occurred in the 2 groups. Cervical internal os plasty is useful in patients with placenta previa accreta due to its simplicity, utility, and effectivity as well as its capacity for preserving fertility. Abstract : Supplemental Digital Content is available in the text